Identification of Coffee Plant Pests in Plantations in The Brenggolo Area, Jatiroto Sub-District, Wonogiri District - Nurhayati, Suci; Wiharti, Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pests that attack coffee plants can have an impact on decreasing productivity and quality of coffee harvests in the area. This study aims to identify coffee plant pests in the Brenggolo area plantation, Jatiroto sub-district, Wonogiri district. This study was conducted for 2 months, from January 2025 to February 2025, at the Brenggolo village coffee plantation, Jatiroto sub-district, Wonogiri district. Data obtained from observations of plant samples and coffee berries attacked by pests, as well as interviews with managers and owners to obtain information on the types of pests and environmental conditions of the plantation land. The results of the study found several pests that attack coffee plants, including Hypothenemeus hampei (Coffee Berry Borer Pest), Xylosandrus compactus (coffee branch borer pest), Ferrisia virgate (Whitefly), Coccus viridis (green aphid pest), Pratylechus coffeae Nematodes (Root Wound Nematodes), and Sanurus indecora jacobi (Planthopper). Pest life is greatly influenced by environmental factors such as altitude, temperature and humidity. The geographical conditions of the Brenggolo plantation, which is at an altitude of 920 meters above sea level, with temperatures ranging between 20°C - 28°C and humidity of 81%, are an environment that supports the development of various types of coffee pests. Identification of pest types and environmental characteristics in the Brenggolo Plantation is expected to be the basis for the formation of an effective pest control strategy. With location-specific pest management, it is expected to increase the productivity and quality of coffee in the area.